(untitled) (Journal of Partial Differential Equations, 2007)
In this article, we prove the Strichartz type estimate for the solutions of linear heat equation with initial data in Hardy space H¹(R^d). As an application, we obtain the full space-time estimate to the solutions of heat equation with initial data in L^p(R^d) for 1 ‹ p ‹ ∞.